Helping Teachers Promote Self-Directed Language Learning: Report of a Fulbright Scholar in Ecuador - Joan Rubin (Profile: Issues in Teachers' Professional Development)
Since Ecuador has determined that it wants to be fully bilingual in ten years, this paper describes the experience of a Fulbright Scholar at a university Language Center in Quito; one helping language teachers improve the language learning skills of their students. The theoretical framework for this work comes from Learner Self-Management (LSM) or Self-Regulation. The scholar details her experience teaching LSM concepts such as SMART goal setting, Task Analysis, Cognitive and Affective Strategies. She provides descriptions of what these language teachers consider the roles of the teacher and that of the learner to be and also what their most critical teaching issues were. She also briefly elaborates the history of the development of learner strategies and the value of metacognitive strategies and knowledge.